The notion of multivalence by Charles Jencks and Kisho Kurokawa – comparison through methods of ‘Abstract Representation’ and ‘Abstract Symbolism’ - Gibert Michael; Naziaty Mohd Yaacob; Zuraini Md Ali (Penerbit Universiti Kebangsaan Malaysia, 2020)
One of the solutions presented in response to the various limitations of the Modernist dogma was the notion of ‘Multivalence’. In the 1960’s various methods related to this were debated and suggested with the underlying motives for architecture to counter Modernist’s puritanism and express the plurality and diversity of society. This paper aims to compare different themes discussed on this topic by two of its representative protagonists, Charles Jencks in the West and Kisho Kurokawa in the Far-East. Through a review in particular of their respective methods of ‘Abstract Representation’ and ‘Abstract Symbolism’, it will be argued that despite sharing similar conclusions, both their approach simultaneously illustrate contrasting world views.